Intercultural Communication Competence: An International Students Experience in Indonesia - Pinariya, Janette Maria; Sutjipto, Aldila Maharani (Bina Nusantara University, 2021)
The research aimed to analyze the intercultural communication competence based on international students’ experience in Indonesia and discussed how, in the globalization era, education had reached a new stage where the process of knowledge exchange had crossed national borders. However, educational institutions were not fully prepared to accommodate these modern needs. Although the study of intercultural communication was not new, concern for new cultural diversity had only received great attention lately, wherein the end, the Intercultural Communication Competence (ICC) in educational fields was still very low and must continue to be explored. The research applied a case and phenomenological study method with a descriptive qualitative approach. The data were gathered through semi-structured interviews and study literature. By analyzing the interactive multicultural building model, supported by the concept of intercultural communication and internationalization of higher education, the research results show that there are still inequalities and differences of opinion as well as an assessment of a three-perspective model that is used as the research focus. It consists of the affective process (intercultural sensitivity), cognitive process (intercultural awareness), and behavioral process (intercultural adroitness). Besides, there are various challenges that must be faced.